Sexuality in school : the limits of education - Gilbert, Jen, 1971- (University of Minnesota Press, 2014)
From concerns over the bullying of LGBTQ youth and battles over sex education, to the regulation of sexual activity and the affirmation of queer youth identity, sexuality saturates the school day. Rather than understand these conflicts as an interruption to the work of education, the author explores how sexuality comes to bear on and to enliven teaching and learning. The author investigates the breakdowns, clashes, and controversies that flare up when sexuality enters spaces of schooling. Education must contain the volatility of sexuality, she argues, and yet, when education seeks to limit the reach of sexuality, it risks shutting learning down. The author explores this paradox by turning to fiction, film, legal case studies, and personal experiences. What, she asks, can we learn about school from a study of sexuality? Ultimately, this book illustrates how the most intimate of our experiences can come to shape how we see and act in the world.--publisher's description.